Czy społeczność uczonych stanowi enklawę? - Chmielewska-Banaszak, Danuta (Szczecin: Wydawnictwo Naukowe Uniwersytetu Szczecińskiego)
Trying to answer the title question an author considers two threads. First, differencesbetween common sense and scientific knowledge are described. Differences thatmake an average man helpless when he tries to understand the majority of scientific discoveries, especially those concerning natural science. Second, the author focuses on the thread of "ivory tower" where scientists are supposed to live. The author tries to prove that this "ivory tower" is a necessary condition of scientific effectiveness. Moreover, the inhabitants of the "ivory tower" are gratified with much more significant immunity to stress, with greater level of happiness and life satisfaction.
Keywords: naukoznawstwo